Effectiveness of Localized Reading Activity Sheets in Enhancing the Reading Skills of Grade 1 Learners A Quasi-Experimental Research Design - Jelie Ann Paulette R Angeles; Karen A Manaig; Sherwin B Sapin; Aberto D Yazon; John Frederick B Tesoro (International Journal of Theory and Application in Elementary and Secondary School Education, 2022)
Covid19 pandemic has brought fears, challenges, and great changes to all sectors, not only in the Philippines but the entire world. The most affected sector would be education since the learning must continue despite the pandemic. It is a great challenge to pursue education and deliver a quality one, especially since the strategies to be used are novel, and teachers should be trained well before their implementation. This study aims to determine the effectiveness of localized Reading Materials among Grade 1 learners through a quasi-experimental research design. The two groups of participants serve as the comparison and experimental groups. A match-pairing technique was used to identify the 30 participants for each group. Weighted average mean, standard deviation, t-test, and independent t-test were utilized to analyze the data. Likewise, Cohen's D was used to determine the effect size or the size of the difference between the two test results. The findings revealed that most of the respondents in the experimental group obtained a higher mean score, while the comparison group was on average. The composite mean score and standard deviation obtained in the experimental and comparison group with a mean score and standard in the descriptive interpretation of experimental and comparison were average. The t-value yielded in the comparative analysis of formative scores of the experimental and comparison groups. The formative mean score of the Effect Size of Large implies the large statistical formative mean score of experimental and comparison groups.